Success stories about severe pneumonia caused by Panton-Valentine leucocidin-producing Staphylococcus aureus - Elisabeth,Paramythiotou (2014)
We describe three cases of community-acquired necrotizing pneumonia which were caused by Panton-Valentine leucocidin-producing strains of Staphylococcus aureus (one of them methicillin sensitive). All cases were successfully treated without any sequelae for the patients due to the prompt initiation of adequate antimicrobial therapy. High suspicion toward this fatal pathogen was the key to the successful outcome of the patients.